Mycobacterium chimaera Encephalitis Following Cardiac Surgery: A New Syndrome. (18th June 2019) - Lau, Darren; Cooper, Ryan; Chen, Justin; Sim, Valerie L; McCombe, Jennifer A; Tyrrell, Gregory J; Bhargava, Ravi; Adam, Benjamin; Chapman, Erin; Croxen, Matthew A; Garady, Cherif; Antonation, Kym; et al.
Abstract: We report the cases of 3 patients with fatal, disseminated Mycobacterium chimaera infections following cardiac surgeries. Progressive neurocognitive decline and death were explained by active granulomatous encephalitis, with widespread involvement of other organs. This syndrome is clinically elusive and, thus, may have caused deaths in prior reported series.